Mechanisms by which Porphyromonas gingivalis evades innate immunity - Abdi, Kaveh (2018)
The oral cavity is home to unique resident microbial communities whose interactions with host immunity are less frequently studied than those of the intestinal microbiome. We examined the stimulatory capacity and the interactions of two oral bacteria, Porphyromonas gingivalis (P. gingivalis) and Fusobacterium nucleatum (F. nucleatum), on Dendritic Cell (DC) activation, comparing them to the effects of the well-studied intestinal microbe Escherichia coli (E. coli). Unlike F. nucleatum and E. coli, P. gingivalis failed to activate DCs, and in fact silenced DC responses induced by F. nucleatum or E. coli. We identified a variant strain of P. gingivalis (W50) that lacked this immunomodulatory activity. Using biochemical approaches and whole genome sequencing to compare the two substrains, we found a point mutation in the hagA gene. This protein is though to be involved in the alteration of the PorSS/gingipain pathway, which regulates protein secretion into the extracellular environment. A proteomic comparison of the secreted products of the two substrains revealed enzymatic differences corresponding to this phenotype. We found that P. gingivalis secretes gingipain(s) that inactivate several key proinflammatory mediators made by DCs and/or T cells, but spare Interleukin-1 (IL-1) and GM-CSF, which can cause capillary leaks that serve as a source of the heme that P. gingivalis requires for its survival, and GM-CSF, which can cause epithelial-cell growth. Taken together, our results suggest that P. gingivalis has evolved potent mechanisms to modulate its virulence factors and dampen the innate immune response by selectively inactivating most proinflammatory cytokines.